The moderating impact of maturation on acute neuromuscular and psycho-physiological responses to simulated soccer activity in academy soccer players - Salter, J.; De Ste Croix, M. B. A.; Hughes, J. B. (European Journal of Sport Science, 2020)
Resource constraints complicate load monitoring practices in some academies, which is problematic based on load-injury associations surrounding periods of rapid non-linear growth. Limited research has explored relationships between maturation and perceived psycho-physiological response to activity and associated neuromuscular performance changes. This study aimed to quantify neuromuscular and psycho-physiological responses to standardised activity and analyse whether dose-responses were moderated by maturation. Fifty-seven male soccer players (age: 14.1 ± 0.9 years; stature: 165 ± 10 cm; body mass, 57 ± 9 kg; percentage of predicted adult height 92.7 ± 5%) from two Elite Player Performance Plan (EPPP) academies completed the youth soccer-specific aerobic fitness test (Y-SAFT60). Countermovement jump (CMJ), reactive strength index (RSI), absolute (ABS) and relative leg stiffness (REL) were measured pre-post the Y-SAFT60 with playerload (PL), heart rate (HR), total distance (TDist) and differential ratings of perceived exertion (dRPE) used as markers of load and intensity. A moderation model was employed to analyse interactions of maturation as a continuous variable. Analysis indicated no significant interaction (p <0.05) between maturation and neuromuscular performance but RPE-Technical demonstrated significant interactions (p = 0.01). Slope analysis indicated four variables (PL, RSI, ABS and REL) that demonstrated significance at various stages of maturation, most notably aligning with peak height velocity (~87-96% PAH). Tentatively, we propose that maturational developments in the neuromuscular system offer some mechanistic explanation to the varied dose-responses observed. It is therefore important that maturation is habitually considered within prescription of training programmes and that further empirical studies are completed to determine maturity specific dose-responses.